IN VITRO ASSESSMENT OF NATURAL HERBAL EXTRACTS FOR ANTIMICROBIAL ACTIVITY - CHALIVENDRA, PALLAVI; GANJIKUNTA, RAVINDRA KUMAR; RAO K., UMAMAHESWARA; PULLAKANAM, RI PHANI TEJASWI (International Journal of Current Pharmaceutical Research, 2023)
Objective: Herbal medicine is still the mainstay of about 75-80% of the whole population, and the major part of traditional therapy involves the use of plant extract and their active constituents against infectious pathogens. Objective: The study aimed to investigate in vitro antibacterial activity of extracts from some medicinal plants against the most common microbial pathogens including MDR bacteria. Methods: The processing of plant materials was performed with the washing, drying and grinding of collected plant materials. The plant extracts were prepared by mixing 10 g of powder to 150 ml of ethanol solvent for 5 h at room temperature and sonicated for 15 min; for prepared test samples under laboratory conditions, the air-dried samples were mixed with the respective solvent (1:15 w/v) for 72 h at room temperature with occasional and then filtered through Whattman filter paper No.1. The obtained extract was freed from the solvent by evaporation under reduced pressure and then resuspended in the appropriate solvent to make the solution of known concentration of 10-50 mg/ml. The extract was stored at 4 °C in airtight glass bottle for the antibacterial assay using the Agar-well diffusion method. Ciprofloxacin was used as a control antibiotic. Results: The growth of K. pneumoniae, Proteus mirabilis, P. aeruginosa and E. coli were inhibited better with the plant extract Tinospora cardifolia leaves than ciprofloxacin antibiotic. Coagulase-negative Staphylococci was inhibited greatly with Costus igneus leaf extract. The growth of Enterococcus faecalic was inhibited significantly with Tridax procumbens leaf extract than ciprofloxacin. Conclusion: The present study indicates Tridax procumbens, T. cordifolia and Costus igneus methanolic leaf extracts were showed strong antimicrobial activity against all the tested cultures. They were rich in primary and secondary constituents. Most of the biologically active phytochemicals were present in methanolic extract. The tested plant extracts were more efficient than standard antibiotic ciprofloxacin used in the current study.